ANALISIS SISTEM PEMBERIAN KREDIT MODAL KERJA PADA PD. BPR BAHTERAMAS KOLAKA UTARA - Nadila, Nadila; Rijal, Abd.; Hamzah, Hajrah (Jurnal Sains Riset, 2024)
This research aims: to determine the system of providing working capital credit to PD. BPR Bahteramas North Kolaka. The variable in this research is the Working Capital Credit Provision System as a single variable. The population of this research is all employees at PD. BPR Bahteramas North Kolaka and customers, while the sample consists of (1) employees who have worked at least 1 year in the credit section of PD. BPR Bahteramas North Kolaka (2) employees who work to handle the process of granting credit to PD. BPR Bahteramas North Kolaka (3) working capital credit customers from 2020 to 2022 who have experience in procedures and lending credit funds to PD. BPR Bahteramas North Kolaka as many as 2 people. Data collection was carried out using documentation and interview techniques. Data analysis was carried out using qualitative descriptive analysis. The results of this research state that the credit granting system to PD. BPR Bahteramas Kolaka Utara has been running well and effectively, in accordance with the procedures, conditions, criteria for whether it is eligible or not and the guidelines that have been set, however there are several things that must be addressed because there are still differences in the recommendation for credit approval and the granting of credit approval.Keywords: BPR, Credit Provision System, and Working Capital Credit